Dietary Euterpe oleracea Essential Oil, the Amazon Açaí, as Feed Additive to Amazonian Ornamental Fish, during Post-Larvae Growing Stage: A Preliminary Study - Lorena Batista de Moura; Jaqueline Gomes Cavalcante; Edileno Tiago de Sousa Nascimento; Isamaira Costa e Silva; Ana Lúcia Salaro; Luís André Luz Barbas; Galileu Crovatto Veras; Daniel Abreu Vasconcelos Campelo (Fishes, 2022)
The present study aimed to evaluate the growth performance, batch uniformity, and survival rate of the Amazonian ornamental fish Heros severus and Pterophyllum scalare during the post-larvae growing stage, fed with diets containing levels of Euterpe oleraceae essential oil (EOO) during 30 days. In the first experiment, 160 H. severus post-larvae were distributed in 16 aquariums (1 L), and in the second, 200 P. scalare post-larvae were randomly distributed in 20 aquariums (1 L). The experiments were carried out in a completely randomized design, with four treatments for H. severus (0.0%, 0.50%, 1.00%, and 2.00% of dietary EOO) and five treatments for P. scalare (0.0%, 0.5%, 1.0%, 2.0%, and 4.0% of dietary EOO), both with four replications and dietary EOO being included in replacing soybean oil. A quadratic effect (p < 0.01) was observed for the final length, length gain, specific growth rate for length, final weight, weight gain, specific growth rate for weight, and batch uniformity for weight for both fish species. As for ornamental fish larviculture, survival rate and batch uniformity are the most important parameters to be considered. For P. scalare and H. severus post-larvae, the inclusion of dietary EOO was beneficial in up to 2.48% and 0.88%, respectively.